The Effect of Learning English on P300 in Children - Marques, Pâmela Mariel; Mattiazzi, Ângela Leusin; Ferreira, Laís; Oppitz, Sheila Jacques; Biaggio, Eliara Pinto Vieira (International Archives of Otorhinolaryngology, 2020)
Introduction Learning a second language is an essential task in today's world, and is experienced by many children. The cognitive auditory-evoked potential (P300) is related to cognitive activity, attention and concentration, enabling the investigation of the effect of a second language on the central auditory pathway.Objective To analyze the effects of learning English on P300 latency and amplitude in children and to correlate them with age, time of exposure to English, and time in class.Method An observational, descriptive, cross-sectional and quantitative study, in which 33 children, aged between 5 and 9 years and 11 months, of both genders participated, 14 of them in the process of learning English (study group) and 19 without this experience (control group). All subjects had their P300 evaluated using the Intelligent Hearing Systems (IHS, Miami, FL, US) Smart EP equipment. A total of 300 binaural stimuli were used in 75 dBnHL, as well as 240 frequent and 60 rare stimuli, using the pairs /ba/ and /di/ respectively.Results There was a statistically significant difference regarding P300 latency between the groups, and children exposed to English classes had lower latency in this component. No statistical difference was found between P300 amplitudes. No correlation was observed regarding age, time of exposure to English, time in class, and electrophysiological responses.Conclusion The Children exposed to English classes had the most stimulating auditory pathway, because their P300 had lower latency, being a resource for the speech therapy clinic.
Keywords: children; event-related potentials; P300; child development; electrophysiology; multilingualism